From Routine to Research Laboratory: Strategies for the Diagnosis of Congenital Fibrinogen Disorders - Casini, Alessandro (Hämostaseologie, 2020)
Congenital fibrinogen disorders (CFDs) encompass a heterogeneous group of fibrinogen defects with a wide spectrum of biological and clinical features. An accurate diagnosis is thus essential to assure the optimal management for the patient. Diagnosis involves a multistep approach starting with routine coagulation assays and assessment of functional and antigenic fibrinogen followed by identification of the molecular anomaly. However, the diagnosis of CFD can be challenging as the sensitivity and specificity of coagulation assays depend on the fibrinogen level as well as on the fibrinogen variant. In addition, patients suffering from CFD have a heterogeneous clinical course which is often unpredictable by routine coagulation assays. To better determine the patient's clinical phenotype, global hemostasis assays and an assessment of the fibrin clot properties are performed in research laboratories. In this review, we summarize the fibrinogen work-up highlighting some common pitfalls and provide an update of the research on CFD.
Keywords: fibrinogen; fibrin; coagulation factors; mutations; diagnosis